2022
DOI: 10.1111/cpr.13241
|View full text |Cite
|
Sign up to set email alerts
|

Tubulin‐binding peptide RR‐171 derived from human umbilical cord serum displays antitumor activity against hepatocellular carcinoma via inducing apoptosis and activating the NF‐kappa B pathway

Abstract: Objectives Hepatocellular carcinoma (HCC) still presents a high incidence of malignant tumours with poor prognosis. There is an urgent need for new therapeutic agents with high specificity, low toxicity and favourable solubility for the clinical treatment of HCC. Materials and Methods The bioactivity of human umbilical cord serum was investigated by proteomics biotechnology and a primitive peptide with certain biological activity was identified. The antitumour effect of RR‐171 was detected by cell viability as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…Signaling enrichment analysis of these associated genes showed that they were enriched in the “AGE-RAGE signaling pathway in diabetic complications” and the “NF-kappa B signaling pathway”. Consistently, several studies showed that these signaling pathways are significantly involved in the development of HCC [ 45 49 ], which further confirms that CAFs may indirectly influence the development of HCC through these CAF-related genes.…”
Section: Discussionsupporting
confidence: 76%
“…Signaling enrichment analysis of these associated genes showed that they were enriched in the “AGE-RAGE signaling pathway in diabetic complications” and the “NF-kappa B signaling pathway”. Consistently, several studies showed that these signaling pathways are significantly involved in the development of HCC [ 45 49 ], which further confirms that CAFs may indirectly influence the development of HCC through these CAF-related genes.…”
Section: Discussionsupporting
confidence: 76%